Effect of selected factors on quality education in public primary schools in kenya - Omae, David Onyancha. (JOOUST, 2018)
The quest to ensure that students achieve decent learning outcomes and acquire values and skills that help them play a positive role in the society is an issue on the policy agenda of the Government of Kenya. The purpose of this study was to explore the effect of selected factors on quality education in public primary schools in Masaba South sub-County, Kisii County, Kenya.The objectives of the study were: to establish the effect of learning resourse on quality education, to determine the effect of teacher resource on quality education, to establish the effect of gender parity on quality education and to determine the effect of pupils' participation in co-curricular activites on quality education.The study adopted descriptive survey research design.The study was guided by the Production Function Theory. A conceptual framework was used to show interrelationships between the dependent and independent variables. The target population was 82 headteachers, 82 standard eight classs teachers and 82 deputy headteachers. Sample size consisted of 68 headteachers, 68 class teachers and 9 deputy headteachers selected through stratified random sampling technique. Questionnaire, interview schedule, and document analysis were used to collect data. Validation was done by expert judgment of the supervisors. Pilot testing was done using Split- Half method by Spearman Brown Formula. A reliability index of 0.8 I 8 and 0.764 of DH and CT respectively were obtained.Quantitative analysis was done using descriptive statistics.Qualitative data was analysed on the basis of themes and sub-themes that emerged from the study. On the concern about the effect of learning facilities on quality education, it was established that there is lack of enough learning resources which has hindered many children from attending school regularly at the end these children give up education. On the issue about the effect of teacher resource on quality education, it was found out that teachers are overloaded, and tend to pay little attention to their work.There are few classroom observations in school. Gender disparity has been enhanced by inappropriate strategies, beliefs, cultures and practices of many diverse individuals as well as changing collective systems, structures in schools and families Co-curricular activities (CCAs) are looked down upon. It is not taken as an integral part of the school program, seen as non-academic, it is informal part of as extras education without time table and compulsory sessions for all students.The study might be useful to teachers, education officers, curriculum developers, parents, sand community leaders in their endeavors in managing the factors which may affect quality education in public primary schools. The researcher recommends that MoE consolidates schools rather than spreading resources thinly for maximum utilization of resources and encourage participation of private individuals to support education. It is also imperative to conduct a study on effect of teacher resource on quality education in public secondary schools in Kenya to broaden the understanding of the study .
Keywords: Quality education in public primary schools in Kenya.; Public primary schools in Kenya.; Kenya.